Autopercepción de la imagen corporal y Habitos Alimentarios en Adolescentes de una Institución educativa-2015 - Alvarado Flores, Leticia Marilyn (2016)
This research was conducted at the Educational Institution Antenor Orrego Espinoza - Laredo with the aim of establishing the relationship between self-perception of body image and eating habits in adolescents. The sample universe consisted of 120 adolescent sex. Scale was used to assess the perception of Body Image and Eating Habits Questionnaire to evaluate developed by the authors for data collection. The results are presented in statistical tables to measure the relationship between variables statistical Chi-Square test was used. After analysis of the results the following conclusions were made: 43 percent of adolescents had a perception of their not altered body image, followed by 47 percent with a perception of body image at risk and 10 percent with an altered perception body image. Regarding eating habits, 61 percent have proper eating habits and 39 percent inadequate. It was found that there were statistically highly significant relationship between the variables. Keywords: Eating habits, body image, adolescents.